ANALYSIS OF SOCIAL PROBLEM IN A GOOD MAN IS HARD TO FIND BY FLANNERY O’CONNOR - Mohamad Hani (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2019)
This study aims to describe the problems of social problems contained in the short story "A Good Man Is Hard to Find" by Flannery O'Connor. This research is descriptive qualitative. The data source obtained in the short story is "A Good Man Is Hard to Find" by Flannery O'Connor. The results of this study are: (1) Family disorganization, due to lack of communication and lack of social relations within the Bailey family, (2) Crime, the Misfit who came out of the prisoner all members of the Bailey family, (3) Social status, the grandmother who is selfish and does everything she can to maintain social status and people's views on her. On the basis of the results, it has been concluded and by using the sociological aspect that the social problem events in the story can be a lesson and improve understanding and interpretation in communicating and socializing in life. This study is hopefully more useful for readers of literary books, especially the work of Flannery O'Connor and writers.